ANALISIS KINERJA KEUANGAN PADA PT. SUCOFINDO (PERSERO) CABANG MAKASSAR - Hasriani Hasriani (AkMen JURNAL ILMIAH, 2012)
To measure the company's ability to generate profits, it can be seen from the ratio of profitability or the profitability of the company. Corporate profitability is measured by the success of the company and the ability to use its assets productively, ie by comparing profits in a period with total assets or number of the company's capital, where the level of high labor turnover can increase its profit